2013
DOI: 10.1108/s0163-786x(2013)0000035007
|View full text |Cite
|
Sign up to set email alerts
|

Images of Surveillance: The Contested and Embedded Visual Language of Anti-Surveillance Protests

Abstract: Images of surveillance the contested and embedded visual language of anti-surveillance protests Book part, Postprint versionThis version is available at http://dx.doi.org/10.14279/depositonce-4955. Suggested CitationDaphi, Priska; Lê, Anja; Ullrich, Peter (2013): Images of surveillance : the contested and embedded visual language of anti-surveillance protests. -In: Doerr, N.; Mattoni, A.; Teune, S. (eds.): Advances in the visual analysis of social movements. -Bingley [u.a.]: Emerald. -(Research in social movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The interplay of the relevant discursive contexts (e.g. the national and the issue-specific ones, see Daphi, Ullrich, and Lê 2013) is decisive for giving movements their shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interplay of the relevant discursive contexts (e.g. the national and the issue-specific ones, see Daphi, Ullrich, and Lê 2013) is decisive for giving movements their shape.…”
Section: Resultsmentioning
confidence: 99%
“…It is thus an illuminating example of how a discursive context shapes modes of sense-making by offering specific frames and not others. Other research has shown these kinds of reminiscences in the visual production of German protest movements against surveillance (Ullrich and Lê 2011;Daphi, Ullrich, and Lê 2013). The most commonplace depictions of surveillance worked with allusions to Germany's past.…”
Section: Skad and Social Movement Researchmentioning
confidence: 96%
“…In this media‐historic constellation, discussions of images in print and electronic media are dominated by an assumed split between commercial and public mass media on the one side and alternative media on the other. Media practices of social movement activists in this phase are characterized by the assumption that social movements have to create counter‐publics to challenge the distorted coverage of what is referred to as “mainstream media.” Accordingly, the research can be divided into contributions focusing on the portrayal of protests in newspapers, magazines, and TV broadcasts (Arpan et al , Corrigall‐Brown and Wilkes , Perlmutter and Wagner , Rohlinger and Klein , Wetzel ) and those investigating activist‐made media such as posters and stickers, leaflets and magazines, and photos and videos (Brunow , Daphi et al , Goodnow , Juhasz , Maclean , Mattoni , Miller , Morrison and Isaac , Ramsey ).…”
Section: The Era Of Television and Videomentioning
confidence: 99%
“…The interplay of the relevant discursive contexts (e.g. the national and the issue-specific ones, see Daphi et al 2013) are decisive for giving movements their shape.…”
Section: Resultsmentioning
confidence: 99%
“…It is thus an illuminating example of how a discursive context shapes modes of sensemaking by offering specific frames and not others. Other research has shown these kinds of reminiscences in the visual production of German protest movements against surveillance (Ullrich and Lê 2011;Daphi, Lê, and Ullrich 2013). The most commonplace depictions of surveillance worked with allusions to Germany's past.…”
Section: Skad and Social Movement Researchmentioning
confidence: 99%